Creating a sustainable & just Lisbon - Crowley, D.; Belchior, C. (Urban Hub 20: Accelerating city change in a VUCA World: Thriveable cities, 2020)
UrbanA is a 3-yrs (2019-21) European funded academic project that revolves around four “Urban Arenas”, each one explores specific themes with a range of “City Makers” to better understand how to create Sustainable and Just cities.